2017
DOI: 10.1063/1.4975427
|View full text |Cite
|
Sign up to set email alerts
|

Chitin extraction and chitosan production from cell wall of two mushroom species (Lactarius vellereus and Phyllophora ribis)

Abstract: Abstract.Chitin is an important polysaccharide found as supporting material in the cell wall of mushrooms. In this study, chitin and chitosan were obtained from the cell wall of two different mushroom species using chemical method and physicochemically characterized. The dry weight chitin contents of the mushroom species were determined as 11.4% for Lactarius vellereus and 7.9% for Phyllophora ribis. Chitosan yields of the chitins isolated from L. vellereus and P. ribis were 73.1% and 75.3%, respectively. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 36 publications
3
15
1
Order By: Relevance
“…Furthermore, the percentage yield of chitosan from chitin in this study ranged from 70.2% to 82%. These results corroborate well with the chitosan yield reported by Erdogan et al, [20].…”
Section: Bactericidal Activity Of Chitosansupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the percentage yield of chitosan from chitin in this study ranged from 70.2% to 82%. These results corroborate well with the chitosan yield reported by Erdogan et al, [20].…”
Section: Bactericidal Activity Of Chitosansupporting
confidence: 93%
“…The percentage of chitin obtained in previous studies ranged from 2.5-12.2% for insects [19], 7.9-11.4% for mushrooms [20] and 33-45% in sh scales [21]. The dry weight of chitin obtained in this study was 11.8%, 9.9% and 39% for banana weevils (BW), mushrooms (MSR) and Nile perch scales (NS) respectively falling within the ranges of the previous studies.…”
Section: Bactericidal Activity Of Chitosansupporting
confidence: 82%
“…From the mushroom powder used, 17.22 g of crude extract was obtained after the first alkaline treatment. The first alkaline treatment was necessary to remove the protein contaminants ( Wu et al, 2004 ; Mohammed et al, 2013 ; Erdogan et al, 2017 ). The amount of crude extract was further reduced after the second alkaline treatment to 6.16 g, which equates to a 12.32% yield.…”
Section: Resultsmentioning
confidence: 99%
“…However, crustacean-sourced chitosan has several disadvantages including heavy metal contamination ( Ghormade et al, 2017 ). Previous studies have shown that chitosan can also be extracted from mushrooms ( Yen and Mau, 2006 ; Erdogan et al, 2017 ) or even mushroom wastes ( Wu et al, 2004 ). Thus, in this study, we produced and tested the effectiveness of mushroom chitosan for flocculating Nannochloropsis cells.…”
Section: Introductionmentioning
confidence: 99%
“…The source and origin mainly determine the crystallinity, purity, and polymer chain arrangement . Up until now, waste crustacean biomass has been the preferred source for chitin isolation; however, techniques to extract chitin from other sources such as sponges, corals, mushrooms, insects, and worms are emerging. Prior to isolation from crustacean waste, contaminants such as proteins, enzymes, minerals, and natural pigments have to be removed.…”
Section: Chitin Biomassmentioning
confidence: 99%